A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties. (1st December 2016) - Mahnken, Rolf; Dammann, Christian
Abstract: Important phenomena in a resin transfer molding (RTM) process for polymeric materials are temperature-dependent visco-elastic effects accompanied by curing. In Part 1 we propose a three-scale model and a comparative study for different meso material properties including bounds and effective material constants. Based on those preliminaries, in this work, Part 2, we present basic relations in a thermodynamic framework for temperature-dependent visco-elastic effects accompanied by curing which is specialized to the scenario of a mechanical-thermal-chemical process. During curing and subsequent mechanical loading, the periodic mesostructure defined by a visco-elastic polymeric matrix and linear-thermo-elastic carbon fibres is taken into account as a representative unit cell (meso-RVE) subjected to thermo-mechanical loading on the mesoscale. Homogenization of the mesoscale by volume averaging is applied to obtain the effective properties for the fully cured composite on the macroscale. In the examples we use DSC-measurements for parameter identification and simulate the curing process as well as mechanical loading of the cured part with the finite-element-method.